Vaxi-eTrack: A Data-driven System for Infant Vaccination Management for Barangay Clinic Pico La Trinidad, Benguet - Acebes, Jayren; Amiao, Jerick Brell; Calias, Sandra; Fianza-Buya, Marielle Angela; Ganado, Linson (Southeast Asian Journal of Science and Technology, 2025)
Efficient management of infant immunization remains a significant challenge in rural communities in the Philippines, where vaccination processes continue to rely on manual, paper-based workflows that often result in inaccurate records, delayed scheduling, weak data security, and limited communication with parents, increasing the risk of missed or delayed vaccinations. Despite the proven success of digital immunization systems in other regions, similar technologies remain underutilized in many local community health centers. This study aims to improve the effectiveness, accuracy, and efficiency of vaccination record management, scheduling, and vaccine inventory monitoring through the development of a digital health information system known as Vaxi-eTrack. The study employed the Rapid Application Development (RAD) methodology, allowing iterative system design, active user involvement, and continuous refinement throughout the development lifecycle. The results revealed SUS scores ranging from 42.5 to 100, indicating varied user experiences but overall positive acceptance. The system achieved a strong overall mean quality score of 4.14 out of 5, with the highest rating in Security, followed by Maintainability, Compatibility, and Scalability, demonstrating strong system performance, reliability, and readiness for broader deployment. Overall, Vaxi-eTrack proved to be an effective digital solution for improving immunization tracking, record accuracy, and service delivery in community health settings, and it is recommended that the system be expanded to other barangays, enhanced with SMS or push notifications, equipped with offline functionality, and continuously evaluated to ensure long-term sustainability and improved public health outcomes.